Culturally diverse board and corporate innovation. (10th March 2021) - Tang, Xiangxi; Shi, Jing; Han, Jianlei; Shu, Ao; Xiao, Fulong
Abstract: We investigate the role of culturally diverse board of directors on firm outcomes in China. We examine whether the diverseness of the educational, professional and cultural backgrounds of board members influences firm innovation. We find that firms whose directors have international experience are more innovative. In addition, the positive cultural diversity effect is more pronounced for returnee directors with postgraduate and science‐related degrees, and longer international work experience. Further, the directors who gain international experience from the countries with higher standards of management practice, corporate governance and intellectual property rights protection have a higher impact on corporate innovative activities.